Material Analysis of Lead Aprons Using Radiography Non-Destructive Testing - Yoshandi, Tengku Mohammad; Hamdani, Hadi Eka; Annisa (Journal of Renewable Energy and Mechanics, 2021)
Lead Apron is a Personal Protective Equipment (PPE) against the effect of Ionizing Radiation such as X-ray. It is essential for the radiation worker to wear Radiation Protection Equipment during commissions involving ionizing radiation. In Pekanbaru, Indonesia the most common radiation worker is Radiographer which help in hospital for diagnose. In this study the Lead Apron analyzed were 6 apron which suspected to have fault due to its inappropriate tend using NDT radiography methods. Radiography methods have advantage of graphic presentation of object unlike any NDT-methods. The image produce from radiography were analyzed using Computed Radiography (CR) and measured the defection of the material. There was only 3 of 6 Lead Apron appropriate for radiation protection.